2018
DOI: 10.1182/blood-2018-99-117257
|View full text |Cite
|
Sign up to set email alerts
|

Phase I Study of the PTEFb Inhibitor BAY 1251152 in Patients with Acute Myelogenous Leukemia

Abstract: Introduction: The critical role of cyclin-dependent kinases in cell division and gene transcription has made them targets for anti-cancer therapies. Positive transcription elongation factor b (PTEFb)/cyclin-dependent kinase 9 (CDK9) plays a key role in transcription of short-lived anti-apoptotic survival proteins and oncogenes such as MYC and MCL-1. BAY 1251152 (BAY) is a potent and highly selective second generation PTEFb/CDK9 inhibitor. We report here the results of a phase I study to determine the safety, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 0 publications
0
17
0
Order By: Relevance
“…Preliminary results from AML patients revealed significant, but short-lived post-treatment reductions in the mRNA levels of MYC (0.5–4 h), PCNA (1–4 h) and MCL-1 (1–3 h). No objective responses were achieved at any doses, despite achieving CDK9 inhibition [ 135 ]. Additionally, BAY-1251152 monotherapy was declared to generate durable remissions of over two years in 2/7 patients with very aggressive relapsed/refractory double-hit DLBCL (Diffused Large B-Cell Lymphoma), following a phase-I trial [ 136 ] ( Table 2 ).…”
Section: Inhibitors Of Cdk9mentioning
confidence: 99%
“…Preliminary results from AML patients revealed significant, but short-lived post-treatment reductions in the mRNA levels of MYC (0.5–4 h), PCNA (1–4 h) and MCL-1 (1–3 h). No objective responses were achieved at any doses, despite achieving CDK9 inhibition [ 135 ]. Additionally, BAY-1251152 monotherapy was declared to generate durable remissions of over two years in 2/7 patients with very aggressive relapsed/refractory double-hit DLBCL (Diffused Large B-Cell Lymphoma), following a phase-I trial [ 136 ] ( Table 2 ).…”
Section: Inhibitors Of Cdk9mentioning
confidence: 99%
“…Bayer also sponsored two phase I studies using BAY1251152 (later renamed VIP152), a follow-up more potent CDK9 inhibitor. The first trial, in patients with advanced blood cancer, failed to show clinical efficacy despite evidence of target engagement (NCT02745743) [ 77 ]. The second trial (NCT02635672) showed a manageable safety profile and signs of antitumour activity [ 78 ], particularly in MYC-driven lymphoma and solid tumours [ 79 ].…”
Section: Rationale For Targeting Tcdks In Crpcmentioning
confidence: 99%
“…Besides adverse effects, many CDK9 inhibitors showed no clear objective responses in patients. No complete response was observed in more than half of 12 phase I studies of compound 1 and three phase II trials of compound 12 . , Although the drug level in the expected therapeutic range was achieved and target engagement was confirmed, there was no objective response in the treatment of AML with compound 8 , a selective CDK9 inhibitor which is currently in an active clinical trial . Overall, clinical trials for the treatment with various CDK9 inhibitors have revealed many detrimental effects, and most of them remain unsuccessful.…”
Section: Cdk9 Inhibitors In Clinical Evaluation For Cancer Therapymentioning
confidence: 99%